Answer with Step-by-step explanation:
Since we have given that
1+4+9+........................+n² =
![(n(n+1)(2n+1))/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/z057l78ogi9axb9qyxcnuo0lu1wdwo9w2d.png)
We will show it using induction on n:
Let n = 1
L.H.S. :1 = R.H.S. :
![(1* 2* 3)/(6)=(6)/(6)=1](https://img.qammunity.org/2020/formulas/mathematics/college/eqvsjvcf6bqt9neocp46pxfmkvxagd13oy.png)
So, P(n) is true for n = 1
Now, we suppose that P(n) is true for n = k.
![1+4+9+...................+k^2=(k(k+1)(2k+1))/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/n30if7ppdep6wudhnlybr3rse5wz0accaa.png)
Now, we will show that P(n) is true for n = k+1.
So, it L.H.S. becomes,
![1+4+9+......................+(k+1)^2](https://img.qammunity.org/2020/formulas/mathematics/college/m69uas6z1gnm7y5dvm1gvlm1e2axvq6hpf.png)
and R.H.S. becomes,
![((k+1)(k+2)(2k+3))/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/z4upvpuj26if3p8uzdwnay2jsyvhhgc6q2.png)
Consider, L.H.S.,
![1+4+9+..+k^2+(k+1)^2\\\\=(k(k+1)(2k+1))/(6)+(k+1)^2\\\\=k+1[(k(2k+1))/(6)+(k+1)]\\\\=(k+1)[(2k^2+k+6k+6)/(6)]\\\\=(k+1)(2k^2+7k+6)/(6)]\\\\=(k+1)(2k^2+4k+3k+6)/(6)]\\\\=(k+1)[(2k(k+2)+3(k+2))/(6)]\\\\=((k+1)(2k+3)(k+2))/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/wiq1avko0m1hj5a1g9mb02pb18jrbb3bm8.png)
So, L.H.S. = R.H.S.
Hence, P(n) is true for all integers n.